Effect of lipoic acid on the some elements in brain tissue of DMBA-induced Guinea Pigs - Çiftçi, Harun; Özkaya, Ahmet; Dayanga?, Alpaslan; Ölçücü, Ali; Çelik, Sait; Şahin, Zafer; Ateş, Sema (KAFKAS UNIVERSITY, 2009)
The oxidative stress, depending on many factors in the etiology of developing cancer caused by reactive oxygen species, plays an important role. In our study, 7, 12-dimethylbenz-[a]anthracene (DMBA) was applied in Guinea Pigs, the alpha lipoic acid (?-LA) has antioxidant properties was investigated protective role against to levels of macro and trace elements in brain. In experiments; totally 24 adult male Guinea Pigs were randomly divided into 4 equal groups (control, DMBA, ?-LA and DMBA+?-LA) containing same numbers. As a result of the analysis in Guinea Pigs brain with the aid of ICP-AES; it was found that the level of calcium from macro elements in DMBA group increased according to control group (P<0.01) and decreased in DMBA+?-LA group (P<0.01), that was in the same levels with control group. Magnesium decreased in DMBA group according to control group (P<0.01) and DMBA+?-LA group and increased in close level of control group. Regarding trace elements, it was seemed that copper levels compared with the control group decreased in DMBA group (P<0.01) and DMBA+?-LA group, it was same level with control group. It was observed that the level zinc decreased according to control group in DMBA group (P<0.01) and increased in DMBA+?-LA group (P<0.01). In addition, it was obtained that levels of iron and manganese in between groups were not significant (P>0.05). As a result, it can be said that from the point of macro and trace elements, the lipoic acid (?-LA) was indicated neuroprotective effect for protection of important organs such as brain from the oxidative stress.
DMBA i?le i?ndüklenmiş kobayların beyin dokusundaki bazı elementler üzerine alfa lipoik asidin etkisi
Keywords: 7,12-dimetilbenz-[a]antrasen; Brain; DMBA; Guinea pig; ICP-AES; Trace Element; ?-Lipoic acid